2023
DOI: 10.1007/s00221-023-06708-4
|View full text |Cite
|
Sign up to set email alerts
|

Neglect dyslexia: whole-word and within-word errors with parafoveal and foveal viewing

Timothy J. Rich,
John Palmer

Abstract: Patients with left-sided neglect dyslexia often omit whole words positioned on the left, termed whole-word errors, or commit errors on the left-sided letters of words, termed unilateral paralexias. In addition, the errors have been shown to be exacerbated by simultaneously presented distractors, which has been interpreted as a failure of selective attention. In two experiments, we examined the dependency of these error types on parafoveal versus foveal viewing. The first experiment used a paradigm with parafov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Other spatial dyslexia can occur because the lesion produces a pathological bias affecting the orienting of attention, producing asymmetric performance. For example, in spatial neglect, a deficit in which patients ignore stimuli located on the contralesional side, patients make frequent errors reading words located in the contralesional space in a text or in a two-word bilateral display [ 13 , 14 , 15 ], or reading letters located in the contralesional part of a single word, mainly involving letter omission and substitution errors [ 16 , 17 ]. This type of deficit, namely neglect dyslexia, is frequent after lesions of the posterior part of the brain, and can sometimes occur without spatial neglect for nonverbal stimuli [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other spatial dyslexia can occur because the lesion produces a pathological bias affecting the orienting of attention, producing asymmetric performance. For example, in spatial neglect, a deficit in which patients ignore stimuli located on the contralesional side, patients make frequent errors reading words located in the contralesional space in a text or in a two-word bilateral display [ 13 , 14 , 15 ], or reading letters located in the contralesional part of a single word, mainly involving letter omission and substitution errors [ 16 , 17 ]. This type of deficit, namely neglect dyslexia, is frequent after lesions of the posterior part of the brain, and can sometimes occur without spatial neglect for nonverbal stimuli [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we were particularly interested in egocentric deficits, because they show the importance of some orienting process to shift attention from one word to the other. Rich and Palmer [ 13 ] found that not only patients made word omission errors when two words, one in each visual hemifield, were presented and only one cued word had to be reported, but they sometimes replaced the target word by the distractor word located on the right ipsilesional side. These intrusion errors were interpreted by the authors as a mislocalization of the contralesional cue or of the contralesional word in the two-word pair.…”
Section: Introductionmentioning
confidence: 99%